HCV Core Protein Induces Chemokine CCL2 and CXCL10 Expression Through NF-κB Signaling Pathway in Macrophages - Song, Xiaotian; Gao, Xue; Wang, Yadong; Raja, Rameez; Zhang, Yaoyu; Yang, Shulin; Li, Miao; Yao, Zhiyan; Wei, Lin (Frontiers in Immunology, 2021)
HCV core protein is the first structural protein synthesized during hepatitis C virus (HCV) infection and replication. It is released from virus infected liver cells and mediates multiple functions to affect host cell response. The innate immune response is the first line of defense against viral infection. After HCV infection, Kupffer cells (KCs) which are liver macrophages play an important role in host innate immune response. Kupffer cells act as phagocytes and release different cytokines and chemokines to counter viral infection and regulate inflammation and fibrosis in liver. Earlier, we have demonstrated that HCV core protein interacts with gC1qR and activates MAPK, NF-κB and PI3K/AKT pathways in macrophages. In this study, we explored the effect of HCV core protein on CCL2 and CXCL10 expression in macrophages and the signaling pathways involved. Upon silencing of gC1qR, we observed a significant decrease expression of CCL2 and CXCL10 in macrophages in the presence of HCV core protein. Inhibiting NF-κB pathway, but not P38, JNK, ERK and AKT pathways greatly reduced the expression of CCL2 and CXCL10. Therefore, our results indicate that interaction of HCV core protein with gC1qR could induce CCL2 and CXCL10 secretion in macrophages via NF-κB signaling pathway. These findings may shed light on the understanding of how leukocytes migrate into the liver and exaggerate host-derived immune responses and may provide novel therapeutic targets in HCV chronic inflammation.